KEHADIRAN SOSIAL DALAM PEMBELAJARAN DARING BERDASARKAN SUDUT PANDANG PEMBELAJAR PENDIDIKAN TERBUKA DAN JARAK JAUH - Niki Raga Tantri (LPPM Universitas Terbuka, 2018)
This research describes whether the social presence can be obtained from online learning of distance education setting. Data in this study employed questionnaire adapted from Rovai (2002) which identified 3 aspects of social presence, namely connectedness aspect, learning aspect, and socio-emotional aspect. Data was taken from 60 students who participated in an 8-weeks online learning. The results showed that all aspects have positive attitudes from students’ point of views. The students experienced connectedness aspect, learning aspect, and socio-emotional aspect in online learning regardless the learning situation which was mostly text-based setting.